2017
DOI: 10.1088/1361-6501/aa7c77
|View full text |Cite
|
Sign up to set email alerts
|

Improving measurement technology for the design of sustainable cities

Abstract: This review identifies and discusses measurement technology gaps that are currently preventing major science leaps from being realized in the study of urban environmental transport processes. These scientific advances are necessary to better understand the links between atmospheric transport processes in the urban environment, human activities, and potential management strategies. We propose that with various improved and targeted measurements, it will be possible to provide technically sound guidance to polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 179 publications
0
14
0
Order By: Relevance
“…Mechanical anemometers (e.g., cup anemometers) Extremely robust and easy to maintain [2]. Insufficient to measure weak and unsteady wind field [3].…”
Section: Technique Advantages Disadvantagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanical anemometers (e.g., cup anemometers) Extremely robust and easy to maintain [2]. Insufficient to measure weak and unsteady wind field [3].…”
Section: Technique Advantages Disadvantagesmentioning
confidence: 99%
“…Able to measure 3-dimensional (3D) wind vector field [5]. Most widely used technique in turbulence measurements [3].…”
Section: Sonic Anemometermentioning
confidence: 99%
See 2 more Smart Citations
“…Different projects in different engineering disciplines and research [ 33 , 34 , 35 , 36 , 37 , 38 ], have shown the need for low-cost but accurate data acquisition systems in recent years, from electrical engineering [ 39 , 40 ], to quality assessment [ 41 ], photovoltaic performance assessment [ 42 , 43 , 44 ] and renewable energy [ 45 ]. It could be also said that these low-cost measurement instruments seems to be increasingly used within the biomedical sector [ 46 , 47 , 48 , 49 , 50 ], and small-satellite space missions [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%